Massive Lower Gastrointestinal Bleeding from Meckel’s Diverticulum with Heterotopic Pancreas: Case Report and a Brief Review of the Literature - Yang, Xing; Guo, Kejian (JOP. Journal of the Pancreas, 2013)
Context Heterotopic pancreas is defined as pancreatic tissue found out of the pancreas proper with no vascular or anatomical connection. It is a rare clinical entity and can be found at any portion of the alimentary system. Case report We describe a case of Meckel’s diverticulum with heterotopic pancreas who presented massive lower gastrointestinal bleeding. Conclusion Lower gastrointestinal bleeding due to Meckel’s diverticulum with heterotopic pancreas is extremely difficult to make a definitive diagnosis preoperatively especially when it onsets rapidly. Image: Mass arising from the distal end of the diverticulum.